Perancangan UI/UX Sistem Informasi Pemesanan Tiket Wisata Punti Kayu Palembang - Michella Valery; Calista Silvia Jaya; Nico Ramadhan Wijaya; Kennan Hamilton; Ahmad Farisi (MDP Student Conference, 2026)
Punti Kayu Tourism Park in Palembang experienced operational constraints in the form of disconnection between the ticket payment system that is still conventional. The impact of this conventional system is related to service and irregularity in visitor data collection. This study aims to design a reservation system interface design and implement a digital payment system using User-Centered Design (UCD). The results of the study showed that the implementation of a payment gateway system into the digital reservation flow can be able to validate transactions automatically. The implementation of this design was significantly effective in reducing the level of service time requirements by 76%, data obtained from an average of 15 minutes to 3.5 minutes. The conclusion of this research is that the system transformation from a conventional to a digital system successfully eliminated administrative obstacles and optimized faster and more accurate service times.